Numerical study on suppressing liquid sloshing of a rectangular tank using moving baffles linked to a spring system. (1st June 2021) - Iranmanesh, A.; Nikbakhti, R.
Abstract: In this paper, feasibility of applying moving baffles linked to a spring system as a mitigation device to suppress liquid sloshing of a container undergoing a harmonic and seismic excitation is investigated numerically using the Coupled Eulerian-Lagrangian (CEL) technique. The interaction between the Eulerian fluid domain where the material can pass through the mesh and the Lagrangian tank domain where the material is supposed to be fixed to the mesh is modelled using the CEL capability of ABAQUS software. Firstly, free sloshing of a rigid/deformable tank is achieved and the numerical results are compared with those of the experiment to validate the numerical simulation quantitatively. Secondly, liquid sloshing of a moving container in absence/presence of moving baffles is simulated and compared with those of the experimental cases qualitatively. Furthermore, the effects of various parameters namely excitation amplitude and frequency, filling ratio, spring stiffness and damping coefficient on both the sloshing kinetic energy and normal forces exerted on the tank wall are investigated separately. The results show that the spring stiffness effects on the kinetic energy of liquid sloshing is minor while the normal force exerted on the left wall can be highly influenced by the spring stiffness. Highlights: Feasibility of using moving baffles to suppress the liquid sloshing is studied. The effects of various parameters on the behavior of liquid sloshing are investigated. The spring stiffness has a minor effect on the sloshing kinetic energy. The normal force exerted on the tank wall is influenced by the spring stiffness. A damper is applied to diminish the normal force oscillations.